Caffie Greene and black women activists - Turner, Kofi-Charu Nat, author.
1 online resource (xxii, 237 pages)
Keywords: "This book uses the life and work of Caffie Greene, one of the most influential grassroots community activists and public health educators in 20th century Los Angeles as a platform to examine the wider story of black women activists in recent United States history. Caffie Green worked to foster the development of unions, Black elected officials and Black youth leaders within the Black Panthers, and worked with a legion of women leaders to further progress in the fields of healthcare, education, youth employment, welfare rights, public transportation, police reform and electoral politics. The book traces Greene's journey from her childhood plantation life in Arkansas; to her emergence as one of the most distinguished civil rights activists in Los Angeles history. It provides in-depth, meticulously researched archival material to amplify the voice of a pivotal woman, and analyses how her contributions impacted the movements of the postwar era. Examining the pedagogical aspects of social protest as the main resource for consciousness raising among historically marginalized youth and adults, Caffie Greene and Black Women Activists asks the essential question: What can we learn about grassroots community organizing that we do not yet know by centering a Black woman like Caffie Greene's life? What are the continuities in Greene's political work between Cold War radicalism, Black Power, and black feminism and that strict binaries like integrationist and black separatist, nationalism and socialism, and feminism and Black Power obscure? This book will be of key interest to students and scholars studying Black activist history, Black Feminism and 20th century United States history"--